Survivorship: Sexual Dysfunction (Male), Version 1.2013: Clinical Practice Guidelines in Oncology - Denlinger, Crystal S. (J Natl Compr Canc Netw, 2014)
Various anticancer treatments, especially those directed toward the pelvis, can damage blood vessels and reduce circulation of blood to the penis and/or damage the autonomic nervous system, resulting in higher rates of erectile dysfunction in survivors than in the general population. In addition, hormonal therapy can contribute to sexual problems, as can depression and anxiety, which are common in cancer survivors. This section of the NCCN Guidelines for Survivorship provides screening, evaluation, and treatment recommendations for male sexual problems, namely erectile dysfunction.